Social organization and scientific practices at the Van Ayanis archeological excavation - Karadaș, Yücel (ANDULI, Revista Andaluza de Ciencias Sociales, 2019)
The archeological excavation in the Ayanis settlement of the Urartu civilisation, which is in today’s Van district of Turkey, is one of the most longlasting excavations in Turkey. Therefore, it indicates the excavation practice in Turkey in the academy of archeology. This study focuses on the Ayanis excavation and analyzes the organization of the excavation team, relationships between the team members, and the way they analyze their object of study. The study also handles how the relationships there are carried to the academy and how the relationships in the academy are affected by them. This study, which is an applied sociological research of archeological practice, aims to induce simple theoretical abstractions from the experiences of the excavation team, which can be seen as a narrow-scale social group. The reseach is conducted using grounded theory, which is seen as more suitable for studying small groups. As such, simple abstract concepts are induced in the light of the in-depth observation of and interviews with the participants of the excavation.